Association between Adiponectin Level and Mean Platelet Volume in Neonates with Respiratory Distress Syndrome: A Prospective Cohort Study - Fares Alyan; Osama A.Zekry; Nashwa R.hassan; Marwa A.Ibrahim (Mashhad University of Medical Sciences, 2023)
Background: Respiratory distress is a serious condition affecting preterm neonates. The present study was designed to evaluate the association between mean platelet volume (MPV) and adiponectin (APN) levels and the development of respiratory distress syndrome (RDS) in preterm neonates. Methods: This prospective cohort study was conducted at a tertiary hospital. The target population was preterm neonates (≤ 34 weeks) admitted to the incubator and diagnosed with RDS. A control group was recruited and composed of age-matched neonates seen at the delivery room and required no admission or ventilatory support. Blood samples were withdrawn on days 1 and 7 of life for a complete blood count and another one for APN level measurement . Results: The study group showed a higher MPV at day 1 and day 7 than the control group (P<0.001) and lower mean APN at day 1 and day 7 than the control group (P<0.001). The MPV had cut-off levels of more than 7.7 (sensitivity of 86.96% and specificity of 100%) and 8.15 (sensitivity of 78.26% and specificity of 91.3%) on days 1 and 7, respectively, to predict RDS. The APN had cut-off levels ≤ 37 (sensitivity of 86.96% and specificity of 60.87%) and ≤ 22.4 (sensitivity of 82.61% and specificity of 69.57%) on days 1 and 7, respectively, to predict RDS. Conclusion: Based on the findings of the present research, the MPV significantly increased while APN levels were lower in preterm neonates with RDS. Both markers predicted RDS development significantly.